Fuel Cells with Proton Exchange Membrane Modeling and Control Techniques - Lalitesh Kumar Singh; Qahtan Adnan Jameel (Edison Journal for Electrical and Electronics Engineering, 2024)
Comprehensive mathematical models with three distinct controllers (PID, FOPID, and fuzzy + PID) for polymer electrolyte fuel cells (PEFCs) are constructed in this work. The models are made to indirectly control the input hydrogen mass flow rate in order to set the output voltage of the PEMFCs at a predetermined value. The simulation results demonstrate how effectively the es-tablished model fits the task of characterizing a PEFC's performance. While the developed control-lers are capable of stabilizing voltage, the fuzzy + PID controller performs better, exhibiting a re-duced overshoot and a faster response time.